STRATEGI GURU DALAM MENGATASI KESULITAN BELAJAR MEMBACA ALQURAN SISWA MDTA MUHAMMADIYAH DESA PANGGORENGAN KEC. PANYABUNGAN KAB. MANDAILING NATAL - Puli Taslim (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2022)
This research was aimed to find out the difficulties faced by students in learning of reciting Al-Quran activity, to find out the factors that cause the difficulties for students in learning of reciting Al-Quran and factors that support the students in learning of reciting Al-Quran, to find out the strategy that conducted by teacher in overcoming the learning difficulties of reciting Al-Quran of grade 3 students at MDTA Muhammadiyah Panggorengan village at year 2019/2020. this research was field research in form of qualitative descriptive. Data sources of this research were primer and seconder data. The data was collected by interviews, observation and documentation. The result of this research showed that the difficulties faced by the grade 3 students of MDTA Muhammadiyah Panggorengan village in learning of reciting Al-Quran activity was difficulty in learning about law of recitation, especially on tafkhim and tarqiq material. The causative factors of the student’s difficulties in learning of reciting Al-Quran were internal and external factor. While the supportive factors in learning of reciting Al-Quran also had internal and external factor. Teacher strategies in overcoming the student’s difficulties were (a). conducting special monitoring, (b). giving motivation, (c). direct the students. Teachers also conducted BTQ activity (recite and write Al-Quran) and literation.